Further evidence for the neuroprotective role of oleanolic acid in a model of focal brain hypoxia in rats - Caltana, Laura Romina (2014)
Ischemic brain injury is a dynamic process involving oxidative stress, inflammation, cell death and the activation of endogenous adaptive and regenerative mechanisms depending on the activation of transcription factors such as hypoxia-inducible factor 1-alpha. Accordingly, we have previously described a new focal hypoxia model by direct intracerebral cobalt chloride injection. In turn, oleanolic acid, a plant-derived triterpenoid, has been extensively used in Asian countries for its anti-inflammatory and anti-tumor properties. A variety of novel pharmacological effects have been attributed to this triterpenoid, including beneficial effects on neurodegenerative disorders - including experimental autoimmune encephalomyelitis - due to its immunomodulatory activities at systemic level, as well as within the central nervous system. In this context, we hypothesize that this triterpenoid may be capable of exerting neuroprotective effects in ischemic brain, suppressing glial activities that contribute to neurotoxicity while promoting those that support neuronal survival. In order to test this hypothesis, we used the intraperitoneal administration of oleanoic acid in adult rats for seven days previous to focal cortical hypoxia induced by cobalt chloride brain injection. We analyzed the neuroprotective effect of oleanoic acid from a morphological point of view, focusing on neuronal survival and glial reaction.